Microscopic life - Walker, Richard, 1951- (Boston : Kingfisher, 2004)
Describes such microscopic organisms as viruses, bacteria, and fungi and the ways they affect human beings and other living things, and also covers the history of the microscope.
Includes index.
Horn Book
Library Media Connection
School Library Journal
8.9
5-8
Keywords: Microbiology -- Juvenile literature; Microbiology; Microbiology